2016
DOI: 10.1007/s00265-016-2228-6
|View full text |Cite
|
Sign up to set email alerts
|

Feeding regime, adult age and sexual size dimorphism as determinants of pre-copulatory sexual cannibalism in virgin wolf spiders

Abstract: Pre-copulatory sexual cannibalism (Pre-SC), where females attack and consume courting males, is considered an extreme case of sexual conflict. Different ultimate causes underlying this phenomenon have been proposed for more than a century and still remain unclear. The main objective of this research was to test the 'adaptive foraging hypothesis' in females of the non-burrowing wolf spider Lycosa fasciiventris. We exposed virgin adult females to either rich or poor diet treatments (differing in prey quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…High rates of precopulatory cannibalism are obviously maladaptive for males, and also for females because they induce male-biased sex ratios by consuming receptive mating partners without accessing their sperm. Strong selection against precopulatory cannibalism is expected to reduce its incidence in nature (Gav ın-Centol et al, 2017;Fisher et al, 2018).…”
Section: Senescence As the Ultimate Cause Of Fmfmentioning
confidence: 99%
“…High rates of precopulatory cannibalism are obviously maladaptive for males, and also for females because they induce male-biased sex ratios by consuming receptive mating partners without accessing their sperm. Strong selection against precopulatory cannibalism is expected to reduce its incidence in nature (Gav ın-Centol et al, 2017;Fisher et al, 2018).…”
Section: Senescence As the Ultimate Cause Of Fmfmentioning
confidence: 99%
“…However, both female aggression towards males and sexual cannibalism correlated with the relative size difference between mates, where females more likely consumed relatively smaller males [16]. The latter indicates sexual cannibalism as a mechanism of mate choice based on male size, a pattern found in some other spider species (e.g., [17,18]).…”
Section: Introductionmentioning
confidence: 79%
“…An increase in a female's tendency to cannibalise males before copulation may therefore be detrimental for population growth rate. Although there is little evidence on whether local conditions can increase pre‐copulatory cannibalism in nature, a recent paper has shown that pre‐copulatory cannibalism rates in female wolf spiders increased significantly in response to feeding regime and relative male size in the laboratory (Gavín‐Centol, Kralj‐Fišer, De Mas, Ruiz‐Lupión, & Moya‐Laraño, ). Alternatively, if sexual cannibalism occurs due to spillover of juvenile aggression, then poor habitats may select for highly aggressive juveniles (Johnson & Sih, ), thereby increasing the rate of adult cannibalism.…”
Section: Discussionmentioning
confidence: 99%